2008
DOI: 10.1196/annals.1414.023
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Origin of Gastric Cancer

Abstract: Gastric cancer is the second leading cause of cancer deaths worldwide. Although the link between Helicobacter pylori infection and gastric cancer is well established, little is known about the early development and detection of this malignant disease. Cancer is the disease of epithelia and recently, it has been suggested that some cancers originate in adult stem cells. Advances have been made in identifying the gastric epithelial stem cells and their immediate descendents, which act as progenitors giving rise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…Gastric cancer is a malignant neoplasm of the epithelia, and it was recently suggested that some cancers originate in adult stem cells [1]. Although the incidence of gastric cancer around the world has decreased, the number of new cases is increasing annually owing to the aging population; from a global perspective, it still ranks as the 4th most common cancer worldwide and the second most common cause of cancer-related death [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer is a malignant neoplasm of the epithelia, and it was recently suggested that some cancers originate in adult stem cells [1]. Although the incidence of gastric cancer around the world has decreased, the number of new cases is increasing annually owing to the aging population; from a global perspective, it still ranks as the 4th most common cancer worldwide and the second most common cause of cancer-related death [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer is a multifactorial disease, with numerous causative variables having been reported, including H. pylori , high-sodium diets, drinking, and smoking [16]. Previous studies in our laboratory have specialized in gastric cancer; therefore the objective of this study was to find new knowledge in the gastric cancer research field.…”
Section: Discussionmentioning
confidence: 99%
“…Advances have been made with respect to identifying the gastric epithelial stem cells and their immediate descendents, which act as progenitors giving rise to mucus-, acid-, pepsinogen-, and hormone-secreting cell lineages. Analyses of some genetically manipulated animal models in which the proliferation and differentiation program of the gastric stem cells was altered by different approaches have provided some clues to the cellular origin of gastric malignancy [21].…”
Section: Hp Stem Cells and Upper Gastrointestinal Carcinogenesismentioning
confidence: 99%